Note on Fractional Green's Function (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we modify some errors on the definition of fractional Green's function in monograph [5], and give the solution of the inhomogenous equation which satisfies the given inhomogenous initial conditions by fractional Green's function.
Keywords: Fractional Green's function; Laplace transform; Mittage-Leffler function.